Treatment and clinical outcomes of patients with acute myeloid leukemia in Finland 2010-2020: A retrospective analysis of electronic health records - Ranti, Juha; Pudas, Hanna; Ranta, Martta; Tuominen, Samuli; Uusi-Rauva, Kristiina; Lammela, Johanna (WILEY, 2025)
Our retrospective study (2010-2020) examined treatment patterns, outcomes, and healthcare resource utilization in Finnish acute myeloid leukemia (AML) patients. Data covered 153 patients diagnosed at Hospital District of Southwest Finland (HDSF) and 107 from other districts who underwent allogeneic stem cell transplantation (aSCT) at HDSF. Of the 153 patients, 56.2% received intensive chemotherapy (IC), while 43.8% deemed ineligible for IC received low-intensity therapies or best supportive care (BSC). Median overall survival for IC patients was 31.2 months, compared to 5.3 months for those under azacytidine and 1.2 months on BSC. Majority (57.5%) of patients over 60 with intermediate/high European leukemia network risk had poor outcomes with IC and couldn't proceed to aSCT. These patients carried the highest costs and hospital resource use per patient month. Most common reasons for transplant ineligibility after IC were refractory disease and infection. Our data provides a comprehensive view on AML treatment landscape from a period when the latest treatment advancements were not yet accessible. The data describes patient groups with poor prognosis and increased healthcare burden, emphasizing the need to improve treatment practices and identify better ways to get more patients to transplant, in a rapidly evolving treatment landscape.